Speech and swallowing characteristics in patients with facioscapulohumeral muscular dystrophy - Vanessa Brzoskowski dos SANTOS; Jonas Alex Morales SAUTE; Laís Alves JACINTO-SCUDEIRO; Annelise AYRES; Rafaela Soares RECH; Alcyr Alves de OLIVEIRA; Maira Rozenfeld OLCHIK (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Although facial muscle weakness is common in patients with Facioscapulohumeral Muscular Dystrophy (FSHD), the literature is scarce on the speech and swallowing aspects. Objective: To investigate speech and swallowing patterns in FSHD and assess the correlation with clinical data. Methods: A cross-sectional study was conducted. Patients with clinical confirmation of FSHD and aged above 18 years were included and paired with healthy control individuals by age and gender. Individuals who had neurological conditions that could interfere with test results were excluded. The following assessments were applied: speech tests (acoustic and auditory-perceptual analysis); swallowing tests with the Northwestern Dysphagia Patient Check Sheet (NDPCS), the Eat Assessment Tool (EAT-10), the Speech Therapy Protocol for Dysphagia Risk (PARD), and the Functional Oral Intake Scale (FOIS); disease staging using the modified Gardner-Medwin-Walton scale (GMWS); and quality of life with the Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36). The correlation between test results and clinical data was verified by non-parametric statistics. Results: Thirteen individuals with FSHD and 10 healthy controls were evaluated. The groups presented significant differences in the motor bases of phonation and breathing. Regarding swallowing, two (15%) individuals presented mild dysphagia and seven (53.8%) showed reduced facial muscles strength. These results were not correlated with duration of the disease, age at symptoms onset, and quality of life. Dysphagia was related to worsening disease severity. Conclusions: FSHD patients presented mild dysarthria and dysphagia. Frequent monitoring of these symptoms could be an important way to provide early rehabilitation and better quality of life.